ADB in Nigeria (Apapa, Lagos : D.E.R., 1994)
This report introduce a fresh banking style in Nigeria and develop a sound bank network in various parts of Nigeria. It also provides financial and technical assistance to the public and private sector organizations within the framework of the government of Nigeria's economic plans and policies.
Cover title.
hza 19/02/2019
Loans
Keywords: Development banks